1977
DOI: 10.1002/app.1977.070210203
|View full text |Cite
|
Sign up to set email alerts
|

Thermal behavior of cotton grafted with vinyl monomers individually and in mixture compositions

Abstract: SynopsisThermal analysis of cotton samples grafted with acrylamide, acrylonitrile, methyl acrylate, and methyl methacrylate individually and in mixture compositions has been carried out. Additional endothermic peaks in the DTA curves characteristic of the polymers grafted were observed. Graft copolymerization of acrylamide and acrylonitrile makes cotton thermally more stable, while in the case of methyl acrylate-and methyl methacrylate-grafted cottons, the initial decomposition starts a t higher temperatures, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
9
0

Year Published

1983
1983
2016
2016

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 30 publications
(9 citation statements)
references
References 14 publications
0
9
0
Order By: Relevance
“…The monomer (MMA) is separated with a separating funnel, dried over anhydrous sodium sulfate and finally fractionated using a fractionating column of about 15 theoretical plates. The phthalo-and biphthalocyanines were prepared according t o a previous publication [7]. The oxides used were analytical grade reagents.…”
Section: Experirnentnlmentioning
confidence: 99%
“…The monomer (MMA) is separated with a separating funnel, dried over anhydrous sodium sulfate and finally fractionated using a fractionating column of about 15 theoretical plates. The phthalo-and biphthalocyanines were prepared according t o a previous publication [7]. The oxides used were analytical grade reagents.…”
Section: Experirnentnlmentioning
confidence: 99%
“…In these studies, however, no systematic characterization of products was reported. It was reported that thermal resistance of the grafted copolymer was improved 18–22. In these studies too, characterization of samples are not enough or thermal analysis data are not fully compared with component homopolymers, i.e., cellulose and polyacrylonitrile.…”
Section: Introductionmentioning
confidence: 99%
“…Grafting of MMA onto cellulose and cellulosic derivatives is well investigated by chemical and radiation methods 1 . Graft copolymerization of MMA and its binary mixtures with different vinyl monomers onto cellulose and cellulosic derivatives using ceric ammonium nitrate as an initiator has been extensively studied 2 . Haque et al 3 grafted MMA onto jute and reported the effect of temperature, initiator concentration and lignin content of jute on percentage grafting.…”
Section: Introductionmentioning
confidence: 99%